Excitonic structure and charge separation in the heliobacterial reaction center probed by multispectral multidimensional spectroscopy - Yin Song (Nature Portfolio, 2021)
The primary energy conversion step in photosynthesis, charge separation, takes place in the reaction center. Here the authors investigate the heliobacterial reaction center using multispectral two-dimensional electronic spectroscopy, identifying the primary electron acceptor and revealing the charge separation mechanism.